Defective imitation of gestures in patients with damage in the left or right hemispheres. Issue 2 (August 1996) - Goldenberg, G
Abstract : OBJECTIVES–Defective imitation of meaningless gestures has repeatedly been demonstrated in patients with apraxia and has been interpreted as being due to a deficit of motor execution. There is, however, controversy as to whether some impairment of imitation also occurs in patients with right brain damage. The aim was to compare defective imitation in patients with left and right brain damage and to explore whether there are qualitative differences between them. METHODS–Imitation was examined in 80 patients with left brain damage (LBD) and aphasia, 40 patients with right brain damage (RBD), and 60 controls for three types of gestures:hand positions, finger configurations, and combined gestures which required a defined hand position as well as a defined configuration of the fingers. RESULTS–Regardless of whether imitation of hand positions and finger configurations were tested each on their own or together, they showed differential susceptibility to RBD and LBD. Whereas imitation of finger configurations was about equally impaired in RBD and LBD, defective imitation of hand positions occurred almost exclusively in patients with LBD, and whereas controls as well as patients with RBD committed less errors with hand positions than with finger configurations, the reverse was the case in patients with LBD. CONCLUSIONS–The pattern of results goes against a deficit of motor execution as being the cause of defective imitation in patients with LBD, as it is difficult to see why such a deficit should affect proximal movements necessary for reaching hand positions more than differential finger movements. An alternative explanation would be that in patients with LBD errors are due to defective mediation by knowledge about the human body whereas in patients with RBD they stem from faulty visuospatial analysis of the demonstrated gesture.